Decolonization as a Factor for European Integration: The Example of the Indochina War - Dao, Duc Thuan (H. : ĐHQGHN, 2019)
The European integration and unification process has been mainly discussed from an internal European perspective as a way of overcome the traditional conflicts, animosities and atrocities of the several European civil wars of the last centuries. This paper will instead present a different approach. The process of European integration during the Cold War will be linked with the process of decolonization systematically. The author is not trying to change the perspectives entirely, but will systematically elaborate the interrelations between decolonization and European integration. For this, the first Indochina War may serve as an example of outstanding importance. French decolonization in Indochina also played an important role in the process of European integration, along with other steps towards decolonization as the Suez Crisis, the war in Algeria etc. This article, will therefore focus on the following issues: firstly, the process of decolonization in Indochina from 1946 to 1954. This part will describe briefly the historical and political context of those countries which engaged directly to that Franco-Vietnam War; secondly, the impacts of decolonization as a factor for European integration from the 1950s onwards; thirdly, the conclusion part suggests an open approach to systematically investigate the inter-connection between the process of European integration during the Cold War and the decolonization issues.